Avaliação do papel da amídala na antinocicepção induzida pelo medo : análises comportamental, imunoistoquímica e farmacológica - Sorregotti, Tatiani (2017)
Exposure of rodents to an open elevated plus maze (oEPM, an EPM with all four open arms) elicits antinociceptive responses, high level of plasma corticosterone and defensive behaviors. However, very little is known about the neural substrates and neurotransmitters that modulate the antinociceptive responses and the defensive behavior of oEPM-exposed animals. It is known that the amygdala plays an important role in the modulation of defensive behavior and pain responses. Accordingly, the Experiment 1 investigated the effects of chemical inactivation of the amygdala [through local injection of cobalt chloride (CoCl2: a nonspecific synaptic blocker)] on the nociception of mice injected formalin into the right hind paw (nociceptive test) and on the defensive behavior of oEPM-exposed mice. Results showed that the amygdala inactivation induced an antinociceptive response in mice injected formalin into the right hind paw when exposed to the glass-cage (safe situation). However, the antinociceptive response was not altered when mice were exposed to the oEPM (aversive situation). In addition, the mice amygdala inactivation reduced the time spent in the proximal area of the arms as well as the frequency of stretched attend postures (SAP), and increased time spent in the arm ends and the head-dipping frequency, suggesting an anxiolytic-like effect. Experiment 2 assessed the pattern of activation of the basolateral (BLA) and central (CeA) nuclei of the amygdala through quantification of Fos protein expression in mice exposed to the oEPM (aversive situation) or injected with formalin into the right hind paw. Fos-positive labeled cells were bilaterally increased in the amygdaloid complex, particularly in the BLA, compared to the control groups. Whereas the neuropeptide corticotropin-releasing factor (CRF) plays a role in the modulatory system of defensive and antinociceptive responses to aversive situations, the Experiment 3 investigated the effects of intra-amygdala microinjections of CRF1 antagonist (CP376395) on these responses on mice exposed to the oEPM. Results showed that the antinociceptive and defensive responses did not change by the blocked of CRF1 in the amygdala. These results are suggestive that the amygdala (in particular, its BLA nucleus) plays a role in the modulation of nociceptive response induced by formalin test and in the modulation of defensive behaviors in oEPM-exposed mice.